Pendekatan Saintifik Dengan Model Pembelajaran Jigsaw Dapat Meningkatkan Kemampuan Passing Bawah Permainan Bolavoli - Andi Atssam Mappanyukki; Muhammad Zulkarnain Zainuddin (SPORTIVE: Journal Of Physical Education, Sport and Recreation, 2021)
This research is a classroom action research which aims to determine the level of student learning outcomes through a scientific approach with the Jigsaw learning model in class VA students at SDN Unggulan Paccinongan Kabupaten. gowa, in the odd semester of the 2019/2020 school year which consists of 36 students. This research was conducted in two cycles where each cycle consisted of four stages, namely: planning, action, observation, reflection. cycle I and cycle II were held for 4 meetings.The learning outcome data was collected using observation sheets, student worksheets, and basic mobility tests at the end of each cycle I and the end of cycle II. The collected data is then analyzed quantitatively by referring to the Benchmark Reference Assessment (PAP). From these data, research on the results of learning the basic motion of passing under the mini volleyball game shows that 4 students who completed learning in the first cycle had completed the study with a percentage (11.11%) and there were 32 studentsdid not complete the study with a percentage (88.88%).whereas in cycle II there were 32 students who completed learning with a percentage (88.88%) and there were 4 students who did not complete learning with a percentage (11.11%). The results of the analysis also showed that there was a significant increase in the learning outcomes of the basic motion of passing under the mini volleyball game in class VA students at SDN Unggulan Pacinongan, Gowa Regency. Based on the results of this study, it can be concluded that the implementation of the scientific approach with the Jigsaw learning model can improve student learning outcomes